Clinical outcome and gut development after insulin-like growth factor-1 supplementation to preterm pigs - Holgersen, Kristine; Rasmussen, Martin Bo; Carey, Galen; Burrin, Douglas G.; Thymann, Thomas; Sangild, Per Torp (Frontiers in Pediatrics, 2022)
Background: Elevation of circulating insulin-like growth factor-1 (IGF-1) within normal physiological levels may alleviate several morbidities in preterm infants but safety and efficacy remain unclear. We hypothesized that IGF-1 supplementation during the first 1-2 weeks after preterm birth improves clinical outcomes and gut development, using preterm pigs as a model for infants. Methods: Preterm pigs were given vehicle or recombinant human IGF-1/binding protein-3 (rhIGF-1, 2.25 mg/kg/d) by subcutaneous injections for 8 days (Experiment 1, n=34), or by systemic infusion for 4 days (Experiment 2, n=18), before collection of blood and organs for analyses. Results: In both experiments, rhIGF-1 treatment increased plasma IGF-1 levels 3-4 fold, reaching the values reported for term suckling piglets. In Experiment 1, rhIGF-1 treatment increased spleen and intestinal weights without affecting clinical outcomes like growth, blood biochemistry (except increased sodium and gamma-glutamyltransferase levels), hematology (e.g. red and white blood cell populations), glucose homeostasis (e.g. basal and glucose-stimulated insulin and glucose levels) or systemic immunity variables (e.g. T cell subsets, neutrophil phagocytosis, LPS stimulation, bacterial translocation to bone marrow). The rhIGF-1 treatment increased gut protein synthesis (+11%, p<0.05), reduced the combined incidence of all-cause mortality and severe necrotizing enterocolitis (NEC, p<0.05), but had limited effects on intestinal morphology, cell proliferation, cell apoptosis, brush-border disaccharidase and peptidase activities, permeability and levels of cytokines (IL-1β, IL-6, IL-8). In Experiment 2, rhIGF-1 treated pigs had reduced blood creatine kinase, creatinine, potassium and aspartate aminotransferase levels, with no effects on organ weights (except increased spleen weight), blood chemistry values, clinical variables or NEC. Conclusion: Physiological elevation of systemic IGF-1 levels for eight days after preterm birth increased intestinal weight/protein synthesis, spleen weight and potential overall viability of pigs, without any apparent negative effects on recorded clinical parameters. The results add further preclinical support for safety and efficacy of supplemental IGF-1 to hospitalized very preterm infants.